Des contradictions dans la perception du système mondial - Korany, Bahgat (Études internationales, 1984)
Emphasizing divergences in the perception of the main characteristics of the world System, this paper concentrates on five main issues: 1) whether the System is getting more integrated or more disintegrated; 2) whether ideology is coming to an end or coming back ; 3) whether the System is multipolar or bipolar ; 4) what are the bases of different poles ; and 5) what help social theory can offer to find the "right" answer. Quantitative data are presented to support the different contentions. The paper's thesis is that even the available data are interpreted differently by different researchers, and this shows the primacy of epistemology, the researchers' basic premises, and the importance of relating the analysis of international relations to issues in philosophy of science.